Teaching (super) wicked problems: authentic learning about climate change. Issue 4 (2nd October 2021) - Cross, Iain D.; Congreve, Alina
ABSTRACT: Climate change is a 'super-wicked' problem associated with challenges including food security, mass migration and biodiversity loss. Young people are increasingly expecting their university education to prepare them to address these challenges. This requires universities to go beyond scientific accounts of climate change, and to engage students in the complex interactions between social, economic and environmental systems. Authentic learning develops students' understanding of 'real-world' challenges and is well aligned with pedagogical traditions in geography. We researched the extent to which climate change is framed as a wicked problem and how students undertake authentic learning about it in UK and Ireland undergraduate geography programmes. Our findings show that while authentic approaches to teaching climate change can be well developed at module level, programme design lacks coherence. Teaching focuses on climate problems rather than progressively scaffolding students' skills for finding effective solutions. We propose that academic developers have significant potential to enhance climate change teaching. We present seven principles for geography programme teams to improve climate change teaching in degree programmes. The wicked problems concept emerged at a time of social unrest and growing environmental consciousness and so remains a powerful way to frame teaching about global challenges.